1,2,4-Thiadiazoles - Schatz, Jürgen; Fritsch, Tabea; Funk, Sebastian (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering, 2022)
In the present chapter, the synthesis, characterization and application of 1,2,4-thiadiazoles is compiled. New insights in structural properties obtained from spectroscopy are reported and information about thermodynamic aspects is updated. The chapter also covers current research about reactivity of 1,2,4-thidiazoles including reactions of the basic ring framework and substituents. Furthermore, new synthetic methods to build up 1,2,4-thiadiazoles are described. The last section briefly summarizes applications and important compounds based on 1,2,4-thiadiazoles.<br
Keywords: Heterocyclic ring synthesisCondensation reactionsNucleophilic substitutionRearrangementsRing contractions

Cucurbiturils in supramolecular catalysis - Funk, Sebastian; Schatz, Jürgen (Journal of Inclusion Phenomena, 2019)